Analysis of Popular Cultural Utilization of TikTok as an Innovative Media in Learning on IPS Students as a Teacher's Prospective - Maharani, Agisti; Rahma, Fitria Ghaida Nur; Rozy, Amirul fachrul; Fitriana, Dina (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The development of digital technology has had a significant impact on learning methods in higher education, particularly for Social Studies Education (IPS) students as prospective teachers. TikTok, as part of the popular digital culture, has the potential to become an innovative learning tool that supports visual, creative, and context-based learning styles. The purpose of this study is to explore the use of TikTok as an innovative medium in learning for Social Studies Education students. This research employs a descriptive qualitative method with a trend study design, integrating a mixed-methods approach to obtain a comprehensive understanding of students' perspectives and tendencies. Data were collected through a Likert scale questionnaire (1–5: Strongly Agree, Agree, Somewhat Agree, Disagree, Strongly Disagree) distributed to active students of the Social Studies Education Program at Tanjungpura University and analyzed descriptively. The results show that most students perceive TikTok as compatible with their digital learning styles and effective as a learning source that connects academic theory with social realities. The use of TikTok has been proven to enhance students' creativity, digital competence, and teaching skills, as well as to motivate and encourage academic collaboration. Overall, utilizing TikTok as an innovative learning tool fosters active, reflective, and contextual learning experiences aligned with the demands of 21st-century education.